BUNGA LAYU DALAM FOTOGRAFI STILL LIFE - Yeti Septo Rini; Setyo Tohari Caturiyanto (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2021)
Flowers are one of the extraordinary forms that are enjoyed by their beauty. Starting from a childhood experience, this work tries to manifest anxiety through the art of photography. The object selected in this work is a lay flower. Wither is where a condition is not fresh or pale. Based on changes in flower color, irregular textures and shapes are interesting to visualize in a photographic work. One of the genres of photography used is still life photography. A work of art that creates an image of an inanimate object or object to make it appear much more alive. The work of this work, uses air-filled media with other supporting objects. The selection of media that contains water is used to facilitate the arrangement in order to achieve aesthetic or beauty value. The values of beauty include unity, complexity, and sincerity in creating such works. All of these things are related to the results in the process of working on the work. The Creation of Withered Flowers in Still life Photography has meaning, not just a visual form without aesthetic value.